Market Reaction of Stock Split Announcement on Listed Companies in Indonesia Stock Exchange - Adhe Erma Laurenchya (IPTEK Journal of Proceedings Series, 2020)
The Issues of stock split is still debatable in the economic field. This is indicated by the mismatch between the theories referred to with practices in the capital market. The focus of the research is to investigate the determinant of the market reaction in the period before and after the announcement of a stock split. This study is designed by qualitative research by using theoretical review based and supporting by previously research. The basic concept underlyed the theoretical review are dimension of trading volume activity, abnormal return, and bid-ask spread. By critical review and classifying the result of previous research, the research found some propositions : (1) stock split have effect on trading volume activity (2) stock split have effect on abnormal return (3) stock split have effect on bid-ask spread